A study on organizational factors for successful execution of human resource management (HRM) practices in private hospitals - Ganapathy, S.; Ashokkumar, M. (International Journal of Engineering and Technology, 2017)
The existing thoughts in Human Resources Management put emphasis on knowledge sharing and team creation instead of individuals, informal learning, individual expertise, flexibility in use of skills, severe limits between healthcare organization and professionals. The organizational climate, efficiency, successfulness and innovativeness are the organizational factors for successful execution of Human Resource Management (HRM) practices in private hospital. The results also show that there is significant difference between socio economic profile of employees of paramedics and organizational factors for successful execution of Human Resource Management (HRM) practices in private hospital. The private hospitals should give conducive working environment to their employees of paramedics through applying advanced technologies, high organizational values, excellent organizational culture, rewards and incentives. In addition, they should promote sharing of knowledge and skills, inter personal relations and leadership among employees of paramedics for successful execution of human resource management practices.Â